2010
DOI: 10.1088/0004-6256/140/1/75
|View full text |Cite
|
Sign up to set email alerts
|

The Antennae Galaxies (Ngc 4038/4039) Revisited: Advanced Camera for Surveys and Nicmos Observations of a Prototypical Merger

Abstract: The Advanced Camera for Surveys (ACS) and the Near Infrared Camera and Multi-Object Spectrometer (NICMOS) have been used to obtain new Hubble Space Telescope images of NGC 4038/4039 ("The Antennae"). These new observations allow us to better differentiate compact star clusters from individual stars, based on both size and color. We use this ability to extend the cluster luminosity function by approximately two magnitudes over our previous WFPC2 results, and find that it continues as a single power law, dN/dL ∝… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
262
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(297 citation statements)
references
References 76 publications
29
262
1
5
Order By: Relevance
“…In order to separate star clusters from individual stars and blends of two or more stars, we follow the general approach described in Whitmore et al (2010) and Chandar et al (2010b), where we construct "training sets" of stars and clusters and use their measured properties to guide the criteria used to automatically select clusters. Figure 4 shows the separation of isolated stars from young, intermediate-age, and old globular clusters that were selected by hand.…”
Section: Cluster Selectionmentioning
confidence: 99%
“…In order to separate star clusters from individual stars and blends of two or more stars, we follow the general approach described in Whitmore et al (2010) and Chandar et al (2010b), where we construct "training sets" of stars and clusters and use their measured properties to guide the criteria used to automatically select clusters. Figure 4 shows the separation of isolated stars from young, intermediate-age, and old globular clusters that were selected by hand.…”
Section: Cluster Selectionmentioning
confidence: 99%
“…Whitmore et al 2010) and give more accurate estimates of cluster ages. However, the Hα image for NGC 1566 is only available in WFPC2 data, with smaller coverage of the galaxy, missing many of our sources.…”
Section: Age and Mass Fittingmentioning
confidence: 99%
“…The knots typically consist of about 30 young massive star clusters with masses greater than 10 4 M and about 60 lower-mass clusters (Whitmore et al 2010). Whitmore et al (2005) found that the cluster to cluster velocity dispersion in the knots is small enough to keep them gravitationally bound leading to merging of clusters in the central region of the knots.…”
Section: An Eo Formation Scenariomentioning
confidence: 99%